Moisture Safety Evaluation of CLT-Concrete Composite Slab - Setragian, Zareh Baghdasarian; Chandra Kusuma, Christianto (My University, 2018)
Timber-concrete composite structures are used with the intention of providing greater capabilities than regular structures composed of a singular material. With its benefits, the combination of the two materials comes with challenges that have to be overcome. Moisture damage is one of the possible risks in combining these materials and it has to be check thoroughly to ensure minimum risk of mould growth. Risk of mould growth is either regulated by specifying the limit of humidity allowed for a certain material, or by growth prediction through numerical modelling. Although both are used in the construction industry, modelling is considered to be a more detailed numerical approach as a means for assessing mould growth. The composite structure focused in this study was a floor section with the combination of CLT and cast-in-situ concrete. The general aim was to identify possible moisture damages on the CLT when exposed to the properties of fresh concrete through transient heat and moisture simulation, and evaluated with a mould growth model. The obtained results were used to evaluate moisture safety by observing the possible levels of mould growth in the construction. Several types of concrete were used as the moisture source: fresh concrete with 0.38 and 0.6 water-cement ratios, and hardened concrete with 0.5 water-cement ratio for a comparison. The vapour diffusion resistance of the fresh concrete materials had to be modified based on the findings of previous studies. This was done to overcome one of the limitations of the program, in which it was not capable to model fresh concrete. Different parameters were tested for the simulations, which were the curing and drying conditions, regional climates, initial concrete condition, addition of vapour retarder and influence of building envelope. No possible moisture damages were observed in the CLT for the case with fresh concrete materials under all the simulated variables. For hardened concrete, at fully saturated condition, it did not achieve moisture safety requirements under all the defined parameters. However, lowering the initial relative humidity of the concrete to 95% was enough for the construction to obtain satisfactory moisture performance. Although the simulation results of fresh concrete showed that it was below the mould growth safety limit under the simulated variables, in reality it could be higher. This was due to the limitation of the program mentioned previously in regards to modelling fresh concrete. Furthermore, the program did not take gravity force into account, and it did not able to model non-porous material such as steel. However,these two factors were assumed not to impact the results by a large margin. Based on these limitations, this study can be further improved by conducting experiments to validate the results.
Keywords: Materialvetenskap; Byggnadsteknik; Materials Science; Building engineering